Progress in the Research of the Spinal Deformity Related to Marfan Syndrome - LIN Guanfeng; WU Nan; WANG Shengru; YANG Yang; ZHANG Jianguo (罕见病研究, 2023)
Marfan syndrome(MFS) is an autosomal dominant systemic connective tissue disease. The incidence rate of MFS is about 2-3 per 10 000. Main cause of MFS is FBN1 gene mutation. About 2/3 of MFS patients have spinal deformities, showing symptoms of scoliosis, thoracic lordosis and lumbar kyphosis, severe spondylolisthesis, dural dilatation and pedicle dystrophy. MFS scoliosis develops with age and may continue even after bone maturation. Conservative treatments such as brace are usually ineffective. Surgical treatment of main curve > 40°-45 °is recommended, but due to the special anatomical structure of MFS patients, such surgical complications as dural leakage, failure of internal fixation and revision surgery are not uncommon.